Pharmacotherapeutic Agents in Diabetes Mellitus: A Narrative Review - Thabassum, A. N. (Journal of Pharmacy Practice and Community Medicine)
Diabetes is a growing public health concern in India and globally. Transition in lifestyle, urbanization have led to soaring of diabetes cases in recent years. International Diabetes Federation estimates that in 2050, around 853 million people will be living with diabetes worldwide. Proper diagnosis and early intervention is essential to prevent irreversible complications of this chronic metabolic disease. A good understanding of the pharmacotherapeutic agents available to treat diabetes will enable clinicians and health care providers in treating diabetes optimally. Research in the field of diabetes has evolved providing many new drugs with promising outcomes. This narrative review explores the pharmacological basis and the clinical importance of medications used in clinical practice.
Keywords: Biguanides; Diabetes mellitus; Pharmacotherapy; Type 2 diabetes